Correlates of Health-Related Quality of Life for Māori Elders Involved in a Peer Education Intervention. Issue 5 (4th May 2019) - Oetzel, John G.; Hokowhitu, Brendan; Simpson, Mary; Reddy, Rangimahora; Cameron, Michael P.; Meha, Pare; Johnston, Kirsten; Nock, Sophie; Greensill, Hineitimoana; Harding, Truely; Shelford, Pita; Smith, Linda Tuhiwai
Abstract : The purpose of this study was to identify social determinant and communication correlates of health-related quality of life for kaumātua (Māori elders) in New Zealand. A total of 209 kaumātua completed a self-report survey of self-rated health, physical/mental quality of life, spirituality, and a series of questions about social determinants (e.g., factors related to income) and communication variables (e.g., loneliness, social support, cultural identity, and perceived burden/benefit). The survey was baseline data for a peer education intervention to help kaumātua work through life transitions in older age. The main findings of this study were that social determinants, particularly difficulty paying bills, accounted for a small amount of variance in physical/mental quality of life and self-rated health. Further, the communication correlates of loneliness, perceived burden, and desired support accounted for about three times as much variance in these two outcomes all with negative associations. Strength of tribal identity, importance of whānau (extended family), and knowledge of tikanga (customs and protocols) accounted for a moderate amount variance in spirituality with positive associations. These findings have important theoretical and practical implications for positive aging.